Numerical study of helical savonius rotor in urban areas / Saif Zeyad Mustafa - Saif , Zeyad Mustafa (2011)
Wind energy has a huge rule in the production of free electricity in urban areas. Usage of helical wind turbine as a power producer is low cost compare to other horizontal wind turbines. Helical savonius wind turbine has a wide range of mechanical design parameters to meet the numerous design requirements. A total of 10 prototypes have been designed using the pro engineer program which are divided into a few mechanical design considerations like aspect ratio, separation gap and Bach cross-section profile, in order to study the behavior of the rotor through using a numerical analysis program like cfdesign. Therefore, this study introduce a new mechanical design considerations to improve the performance over (cp=0.2) using computational fluid dynamics (CFD) and analyze the results, helical rotor found to have (cp=0.26) with a Bach cross-section of (90o to 20o), considering the wind resources in Malaysia.